Detection of Hg2+ Metal Ions Using Silver Nanoparticles Stabilized by Gelatin and Tween-20 - Lilis Sulistiawaty; Sri Sugiarti; Noviyan Darmawan (Indonesian Journal of Chemistry, 2015)
Silver nanoparticles were synthesized by reduction method using glucose as reducing agent for precursor AgNO3. This research was aimed at comparing the stability and performance of silver nanoparticles with stabilizer gelatin (Gelatin-AgNPs) and tween-20 (Tween-AgNPs) produced from the synthesis to the silver nanoparticles without stabilizer, and applying the Gelatin-AgNPs and Tween-AgNPs to detect heavy metal in water sample. The silver nanoparticles produced were characterized using UV-Vis spectrophotometer and Transmission Electron Microscopy (TEM). From measurement of UV-Vis spectrophotometer, the absorbance wavelength of silver nanoparticles (AgNPs) appeared in range 411 nm, Gelatin-AgNPs in 417 nm, and Tween-AgNPs in 420 nm. The identification using TEM showed the average size for each AgNPs, Gelatin-AgNPs, and Tween-AgNPs was 11.73, 9.68, and 17.54 nm, respectively. The result showed that Gelatin-AgNPs has better stability compared to Tween-AgNPs. The reaction of Gelatin-AgNPs and Tween-AgNPs with several ions showed color changes of Gelatin-AgNPs and Tween-AgNPs occurred only on addition to Hg2+ metal ions solution. Based on the experiment of Hg2+ metal ions determination this method has limit of detection of 0.45 mg/L for Gelatin-AgNPs and 0.13 mg/L for Tween-AgNPs.